2020
DOI: 10.1111/jfbc.13400
|View full text |Cite
|
Sign up to set email alerts
|

HPLC analysis, cytotoxicity, and safety study ofMoringa oleiferaLam. (wild type) leaf extract

Abstract: The study was planned to evaluate toxicity of M. oleifera leaf methanol extract in Wistar rats, cytotoxic potential and chemically characterize it. Acute toxicity study revealed no mortality at 2,000 mg/kg dose. In subchronic toxicity, 150, 300, and 600 mg/kg extract were administered in both sexes for 90 days. A decrease in body weight, cholesterol, and low-density lipoproteins, as well as an increase in the platelet count were observed. The histology of heart, lung, and kidney was normal. The oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
0
16
0
1
Order By: Relevance
“…Additionally, Nair et al (2020) have recently demonstrated that compounds presented in moringa extracts are able to pass across Blood-brain-barrier (BBB) and to reach its pharmacological target [ 55 ]. Regarding the safe toxicological profile of moringa, doses of up to 2000 mg/kg of methanol and aqueous leaf extract were safe in animal studies [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Nair et al (2020) have recently demonstrated that compounds presented in moringa extracts are able to pass across Blood-brain-barrier (BBB) and to reach its pharmacological target [ 55 ]. Regarding the safe toxicological profile of moringa, doses of up to 2000 mg/kg of methanol and aqueous leaf extract were safe in animal studies [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…It attenuated the hematopoietic changes, hepatic and renal dysfunction, MDA formation, and DNA fragmentation induced by TMX. Saleem et al [ 62 ] confirmed the safety of MLE, showing that the acute and sub-chronic administration of MLE to Wistar rats did not appear to result in notable abnormalities in organ relative weights, or hematological and biochemical parameters. The findings of several studies also agreed with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Six solvent extracts of cluster bean were used for reverse-phase HPLC to quantify the phenolic and flavonoids contents ( Proestos et al, 2005 ). Reaction mixture of each extract was prepared in methanol and filtered through .2 μm syringe membrane filters ( Saleem et al, 2020 ) before injecting into HPLC. The C18 column (250 × 4.6 mm internal diameter) of 5 μm film thickness was used with temperature control system set at 30°C.…”
Section: Methodsmentioning
confidence: 99%